Devulcanizaiton of waste tread rubber in supercritical carbon dioxide: Operating parameters and product characterization. (September 2015) - Liu, Zhijun; Li, Xiang; Xu, Xiaofei; Wang, Xiaojuan; Dong, Chao; Liu, Fengxia; Wei, Wei
Abstract: Waste tire rubber was devulcanized by using supercritical carbon dioxide as a reaction medium. The influence of reaction temperature, pressure, time and diphenyl disulfide concentration on devulcanizaiton was studied, and their interactions were demonstrated by the 2-level full factorial experiments. It is found that diphenyl disulfide concentration is the most important factor; the crosslink density of gel is greater than that of original tire rubber when the diphenyl disulfide concentration is below 10 g L −1 ; the change of pressure above critical point almost has no effect on devulcanization. The reaction temperature determined the type of crosslink scission. Then, the products were characterized by Fourier Transform Infrared Spectroscopy, Differential Scanning Calorimetry and Scanning Electron Microscope. The glass transition temperature of devulcanization increase significantly. The fraction surface of devulcanized rubber presents the different morphologies for whether swelled by carbon dioxide or not. Finally, the reaction mechanism and model were developed for devulcanizing process. These results suggest that supercritical carbon dioxide brings diphenyl disulfide into the crosslink network, and the devulcanizing reaction took place on the surface and inside of the rubber at the same time, which led to the sol with higher molecular and lower polydispersity index.